Genomic exploration of pediatric neurological disorders: a case series - Naresh Tayade; Gautham Manoj; Akshay Kewat; Anjali Krishna A; Rajiv Devulapalli; Somesh Kumar; Sunil Kumar Polipalli; Bipin G. Nair; Obul Reddy Bandapalli; Prashanth Suravajhala (Journal of Medical Case Reports)
Abstract Background Pediatric neurological disorders include neurodegenerative diseases causing cognitive impairment and vision loss. They are one of the important causes of morbidity and mortality in children with diverse etiologies. Diagnosis is difficult despite genetic work, and a final diagnosis can be achieved in only 60% of cases. Case presentation We explore three Indian cases of pediatric neurological diseases (with age presented at the clinic), viz. arthrogryposis (8 years), autism (18 months), and congenital bilateral cataract (3 years), by analyzing clinical exomes. In this work, we attempt to understand rare neurological disorders in an Indian pediatric cohort using exome studies. Conclusion We used our benchmarked CONVEX pipeline for screening consensus variants, wherein EIF2B2 was found to be inherently pathogenic. We map the association of variants and genes and disease correlation to neuroleptic malignant syndrome, which matches the phenotype to the cases.